Identifikasi Mikoriza Vesikular Arbuskular pada Rhizosfer Tanaman Lamtoro (Leucaena leucocephala) dan Kaliandra (Calliandra calothyrsus) serta Perbanyakannya dengan Media Zeolit - DHARMAPUTRI, NI WAYAN PUSPARINI; WIJAYA, I NYOMAN; ADIARTAYASA, WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Vesicular Arbuscular Mycorrhizae Identification of Lamtoro (Leucaena leucocephala) and Kaliandra (Calliandra calothyrsus) Rhizosphere and Its Spore Multiplication in Zeolit Media Songan village was located in the district of Kintamani, Bangli. The plants population were dominated by lamtoro and kaliandra. This plant was included in the Fabaceae (Leguminoseae) family which capable of forming nodules and symbiotic association to mycorrhizae. This study aimed to determine the types mycorrhizal of rhizosphere lamtoro and kaliandra plants and determine the effectiveness of zeolite media and corn symbiont plant in propagation of VAM. The experiment was conducted from Desember 2014 to Februari 2015, in the Laboratory of Genetic Resources Unit and Molecular Biology University of Udayana. Spore isolation was done by conducting wet sieving method. Roots colonization percentages were calculated by root staining method and spores multiplication through trapping culture method. The results showed that VAM spores found in the rhizosphere lamtoro plants are three genera that resembled Acaulospora, Glomus, and Scutellospora whereas in the rhizosphere of kaliandra plants found two genera that resembled Acaulospora and Glomus. Mycorrhizal structures found in the rhizosphere of lamtoro and kaliandra plants were vesicles and inner spores.VAM from the rhizosphere of lamtoro and kaliandra plants can be reproduced using zeolite media and corn symbionts.
Keywords: Rhizosphere; Glomus; Acaulospora; Scutellospora; Zeolite